2011
DOI: 10.1017/s2045796011000746
|View full text |Cite|
|
Sign up to set email alerts
|

Age of onset of mental disorders and use of mental health services: needs, opportunities and obstacles

Abstract: Purpose of review. In this review, we provide an update of recent studies on the age of onset (AOO) of the major mental disorders, with a special focus on the availability and use of services providing prevention and early intervention.Recent findings. The studies reviewed here confirm previous reports on the AOO of the major mental disorders. Although the behaviour disorders and specific anxiety disorders emerge during childhood, most of the high-prevalence disorders (mood, anxiety and substance use) emerge d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
258
0
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(303 citation statements)
references
References 80 publications
7
258
0
18
Order By: Relevance
“…High rates of mental health problems among adolescents and young adults are well documented, with threequarters of all lifetime cases emerging before 24 years [1] [2]. A review of the global burden of disease [3] found that the main cause of disability-adjusted life years (DALYs) across global regions for young people aged 10 -24 years was neuropsychiatric disorders, accounting for 45% of all DALYs in this age group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High rates of mental health problems among adolescents and young adults are well documented, with threequarters of all lifetime cases emerging before 24 years [1] [2]. A review of the global burden of disease [3] found that the main cause of disability-adjusted life years (DALYs) across global regions for young people aged 10 -24 years was neuropsychiatric disorders, accounting for 45% of all DALYs in this age group.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the global burden of disease [3] found that the main cause of disability-adjusted life years (DALYs) across global regions for young people aged 10 -24 years was neuropsychiatric disorders, accounting for 45% of all DALYs in this age group. Without appropriate intervention these mental health problems are likely to significantly impact on the life of the young person and will continue well into adulthood [1]. Fortunately, evidence-based treatment approaches can reduce symptom severity and the impact on a young person's life [4].…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com Vinocur e Pereira (2011), geralmente, Ă© responsabilidade dos pais reconhecer que o filho tem um problema e procurar o tratamento adequado, mas muitos nĂŁo se atĂȘm a eles acreditando que as alteraçÔes emocionais e comportamentais sĂŁo inerentes Ă  adolescĂȘncia. Nesse sentido, faz-se importante outros olhares, como o de professores, que, em função do tempo que passam com seus alunos, poderĂŁo identificar sinais que demandam encaminhamento para avaliação (Vigoya, 2005), contribuindo para intervençÔes precoces que podem reduzir a gravidade do problema e prevenir o desenvolvimento de comorbidades (Girolamo, Dagani, Purcell, Cocchi, & McGorry, 2012). Nesse sentido, o contexto escolar, alĂ©m do familiar, tem sido identificado como estratĂ©gico para prevenção e promoção de saĂșde mental de crianças e adolescentes.…”
unclassified
“…This task is all the more challenging as not only psychosis, but also most other mental illnesses begin in adolescence [6]. Furthermore, as adolescence is a period of life characterized by multitudinous variants in behaviour, developing diversity of contextual thinking, and frequent emotional turmoil, patients that are referred to early psychosis services for risk assessment may simply experience symptoms that belong to the large scope of phenomena inhering in adolescence.…”
Section: Introductionmentioning
confidence: 99%